2020
DOI: 10.1097/wnp.0000000000000696
|View full text |Cite
|
Sign up to set email alerts
|

The Neurophysiological Severity of Carpal Tunnel Syndrome Cannot Be Predicted by Median Nerve Cross-Sectional Area and Wrist-to-Forearm Ratio

Abstract: Purpose: The median nerve cross-sectional area at the wrist (CSA) and the wrist-to-forearm ratio of the cross-sectional areas (WFR) are ultrasound parameters used in the diagnosis and grading of carpal tunnel syndrome. This study aimed to determine the diagnostic accuracy of the CSA and WFR as well as to compare their diagnostic value.Methods: A retrospective evaluation was conducted of a cohort of 218 patients who had undergone nerve conduction studies (NCSs) and an ultrasound of the median nerve. The examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…In 1950, the Phalen reported a large number of CTS cases and gave the first detailed description of the etiology, diagnosis, and treatment of CTS. The patient was diagnosed by the clinician [ 7 ]. However, due to the different diagnostic standards and testing methods, the real incidence rate cannot be accurately obtained.…”
Section: Introductionmentioning
confidence: 99%
“…In 1950, the Phalen reported a large number of CTS cases and gave the first detailed description of the etiology, diagnosis, and treatment of CTS. The patient was diagnosed by the clinician [ 7 ]. However, due to the different diagnostic standards and testing methods, the real incidence rate cannot be accurately obtained.…”
Section: Introductionmentioning
confidence: 99%
“…The strength of correlation between wCSA and the severity of CTS has varied greatly in previous studies ( Bayrak et al, 2007 , Billakota and Hobson-Webb, 2017 , El Miedany et al, 2004 , Ha et al, 2017 , Kang et al, 2012 , Karadağ et al, 2010 , Kwon et al, 2014 , Lee et al, 2005 , Mhoon et al, 2012 , Padua et al, 2008 , Pinilla et al, 2008 , Ting et al, 2019 , Wiesler et al, 2006 , Żyluk et al, 2014 ). In our previous study ( Martikkala et al, 2020 ), we found that the variance of the wCSA as well as the variance of WFR grows as CTS severity increases. In our present study, which included only wrists with moderate to extreme CTS, the wCSA and WFR did not correlate with the severity of CTS or with the axon loss of the MN.…”
Section: Discussionmentioning
confidence: 66%
“…In our previous study ( Martikkala et al, 2020 ), we found that the wCSA and WFR correlate with neurophysiological CTS severity. However, in severe CTS, the reliability of the wCSA and WFR as indicators of CTS severity was impaired.…”
Section: Introductionmentioning
confidence: 60%
“…There are conflicting findings in the current literature regarding ultrasound parameters and EDX severity grading as reported in the introduction. Studies by Mhoon 22 and Martikkala 16 did not find any correlation whereas the studies by El Miedany, 23 Ting, 24 and Moschovos, 17 on the other hand, did. These studies all used different EDX protocols and none of them utilized the CSI or Bland protocols, which have been shown to predict surgical outcome 6,7 .…”
Section: Discussionmentioning
confidence: 81%
“…Roll and colleagues concluded that the lack of standardized methodology has made it difficult to determine the diagnostic utility of ultrasound in CTS evaluation 13 . Additionally, the current literature is conflicting on whether ultrasound parameters can be used to determine CTS severity grading, 12,14‐17 which limits utility of ultrasound diagnostics because severity grading may be used to predict surgical outcome and guide treatment 6,7,18,19 . This indicates that further studies are necessary to characterize the diagnostic accuracy of the ultrasound measurements.…”
Section: Introductionmentioning
confidence: 99%